2020
DOI: 10.3389/fsoc.2019.00089
|View full text |Cite
|
Sign up to set email alerts
|

Paradigm-Specific Risk Conceptions, Patient Safety, and the Regulation of Traditional and Complementary Medicine Practitioners: The Case of Homeopathy in Ontario, Canada

Abstract: While the principle of risk reduction increasingly underpins health professional regulatory models across the globe, concepts of risk are neither static nor epistemically neutral. Conventional biomedicine's risk conceptions are substantially rooted in principles of scientific materialism, while many traditional and complementary medicine systems have vitalistic epistemic underpinnings that give rise to distinctive safety considerations. The statutory regulation of traditional and complementary medicine provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…We interpret these training and linguistic variables as a rough proxy for clinicians’ immigrant status from the aforementioned regions. This interpretation is reasonable given that traditional East Asian medicine and acupuncture are regulated professions in China and other East Asian countries [ 7 ]; and, homeopathy is similarly regulated in both India and Pakistan [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We interpret these training and linguistic variables as a rough proxy for clinicians’ immigrant status from the aforementioned regions. This interpretation is reasonable given that traditional East Asian medicine and acupuncture are regulated professions in China and other East Asian countries [ 7 ]; and, homeopathy is similarly regulated in both India and Pakistan [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It would be worth interrogating in future what factors may be contributing to the comparatively low earnings of the province’s T&CM professions, in addition to the fact that these occupations work outside of the provincial public health care reimbursement system. One factor warranting exploration is the impact of these groups’ socio-cultural marginality—in particular for homeopaths, the plausibility of whose occupational epistemology is widely contested by biomedical scientists [ 43 ]. Another potential income-relevant factor warranting exploration is the availability of third-party insurance reimbursement for these professions’ services.…”
Section: Discussionmentioning
confidence: 99%
“…A similar range of research concerns was found, such as the content of accreditation standards [ 309 , 310 ], implementing evidence-based national examinations [ 24 , 311 313 ], regulatory strengthening [ 314 , 315 ], and regulating scopes of practice [ 297 , 304 , 316 319 ]. Studies note some of the policy challenges and adjustments required when applying statutory registration to the T&CM occupations, such as evaluating risk, protecting traditional knowledge, applying flexible language requirements, or delivering care to underserved populations [ 291 , 297 , 316 318 , 320 – 326 ].…”
Section: Resultsmentioning
confidence: 99%
“…19 Second, regulation should be part of a broader policy framework for TCIH that also defines and protects indigenous practices. This may include, among others, the protection of indigenous practices, including from unfair use and misappropriation; safety that includes active negotiation of paradigm-specific risk conceptions 20 ; appropriate promotion of practice; and sustainable use of plant and animal species.…”
Section: Discussionmentioning
confidence: 99%